Decision Support System Pemilihan Lokasi Terminal Check In Pelabuhan Merak Dengan Metode Delphi - Henricus Bambang Triantono (Conference In Business, Accounting, And Management (CBAM), 2012)
Decision Support Systems or DSS is a form of management information systems specificallydesigned to support planners and stakeholders in decision-making. DSS may reflect different concepts of decision-making and conditions vary, and will be very useful for semi-structured or unstructured problems in which the decision process is enhanced with interactive dialogue between the DSS user. The Delphi method is based on structural this surveys and makes use of the intuitive available information of the participants, who are mainly experts. Transport between islands can not be separated from the transport that connects the islands as a bridge, of which the most important is the movement of ships crossing through the form of roll on roll off ferry is more commonly known as roro ship or roro ferry. Medium transport in the island can also take advantage of the great rivers or lakes and reservoirs that are not small.In 2008 there was a barrier between Merak crossing implementation - and worse Bakauheni in 2011 that resulted in long queues for days. This problem arises as a result of lack of sensitivity of the monitoring system so that the flow is not expected occurrence of resistance in these services. The problem occur buildup of heavy congestion of passengers and causing damage to all parties. To solve these problems it is necessary to include steps to create / build Terminal Chek-in outside the port of Merak.Keywords: DSS, heavy congestion , terminal chek-in, delphi method